Vulvar syringomas in an Indian female - Mendiratta Vibhu; Harjai Bhawna; Gupta Tanvi (Wolters Kluwer Medknow Publications, 2007)
Syringomas are benign appendageal tumors of the eccrine sweat glands which are more common in women over the extragenital sites like the periorbital, cervical and axillary areas and the chest. Vulvar syringomas although not rare, are reported uncommonly perhaps owing to a missed diagnosis. Vulvar Syringomas are remarkable for pruritus. A case of multiple vulvar syringomas is reported in an Indian female.